DESIGN DECISION SUPPORT SYSTEM FOR A MARKETPLACE SELECTION USING THE ELIMINATION METHOD ET CHOIX TRADUISANT LA REALITE - Ramadhan, Rizal Furqan; Eliyen, Kunti (Jurnal Pilar Nusa Mandiri, 2023)
The marketplace phenomenon has become exciting, especially for the younger generation actively browsing the internet. In the past, humans had to meet when making buying and selling transactions. With the emergence of a marketplace, it was enough to use smartphone media to make buying and selling transactions. Along with the times, many developers have created marketplaces with different characteristics. So it is necessary to research to provide a good marketplace recommendation following the community's needs. The needs of the average community to fulfil their daily activities, especially in terms of clothing and electronic goods at affordable prices on the marketplace application. The computational method used in this study is the Elimination Et Choix Traduisant La Realite method based on the Decision Support System as a database controller. The research results obtained the highest score in the Shopee marketplace, namely 77.5, followed by the Tokopedia marketplace with a value of 71. Calculations in the ELECTRE method involve a set of concordance and discordance stages that make it different from other methods. The value for each alternative comes from a questionnaire filled out by 63 Z generations. Generation Z is considered a generation that is close to technology.